Investigation of Accounting Theory Issues in the Works of Lithuanian Authors - Mackevičius, Jonas; Subačienė, Rasa; Tamulevičienė, Daiva (Buhalterinės apskaitos teorija ir praktika, 2018)
[only abstract in English; full article and abstract in Lithuanian]The article focuses on how Lithuanian authors investigate the most important issues of accounting theory. The analysis of Lithuanian authors’ textbooks and educational books examining the topics and issues of accounting theory showed that designation, volume, consistency of teaching, etc. differ. The issues of accounting significance, types, principles or policies are examined the most frequently. Lithuanian authors have introduced plenty of new and original thoughts and ideas on these issues which enrich accounting theory. Among them these are noteworthy: introduction of new accounting principles, more detailed definition of financial and management accounting, broader designation of accounting significance for the needs not only of a company, but of society, etc. These differences are explained not as much by the different approaches towards accounting theory but rather by the events and available information of the period in which the books were written. Examination of accounting theory issues in the works of Lithuanian authors is important because methodologically sound disclosure of their essence in textbooks and educational books is of key importance for training highly qualified experts of accounting.